IN VITRO STUDIES ON PHYTOCHEMICAL, ANTIOXIDANT, AND ANTIBACTERIAL PROPERTIES OF ADANSONIA DIGITATA L. FRUIT PULP AND LAWSONIA INERMIS L. LEAVES EXTRACTS. - Abdelrahim, Musab (Student’s Journal of Health Research Africa, 2025)
Background Plant materials are widely used for their healing power, and many studies have shown that compounds isolated from plants exhibit variable biological properties. The present work was aimed to determine the preliminary phytochemical contents, evaluate the antioxidant capacities, and investigate the antibacterial activities of Adansonia digitata L (Bombacaceae) fruit pulp and Lawsonia inermis L (Lythraceae) leaves extracts. Methods Plant materials were first extracted (separately) by methanolic maceration, then the obtained extracts were utilized for preliminary phytochemical screening tests, in vitro DPPH antioxidant assay, and to determine their antibacterial activities against Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, and Pseudomonas aeruginosa using the plate hole diffusion assay. Results The preliminary phytochemical screening for L. inermis leaf extract revealed the presence of tannins, flavonoids, alkaloids, steroids, and saponins, while A. Digitata fruit pulp extract gave positive results for tannins, saponins, cardiac glycosides, terpenes, and flavonoids. Both plant materials exhibited concentration-dependent radical scavenging activity with relatively similar capacities, which is equivalent to the standard (quercetin) at all concentrations (5, 10, 50, 125, and 250 µg/ml). The recorded growth inhibition for A. digitata was 19mm against Klebsiella pneumoniae, 18mm for Staphylococcus aureus and Proteus mirabilis, 15mm for Pseudomonas aeruginosa, and 14mm against Escherichia coli. For L. inermis, the inhibition zone was 25mm against Staphylococcus aureus, 20mm for Escherichia coli, 19mm for Proteus mirabilis, 16mm for Pseudomonas aeruginosa, and 13mm against Klebsiella pneumonia. Conclusion The obtained findings could justify the pharmacological properties and may provide the rationale for some ethnomedicinal uses of these plant products. Recommendation Further investigations should be performed as they could enhance the medicinal importance and evaluate the traditional values of these plants.